KONVERGENSI SIMBOLIK DI HAUL GURU TUA - Syamsuri, Syamsuri (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
The unification of the flow of information in the arena of the celebration of Sayyid Idrus bin Salim Aljufrie's death day is on the agenda every year so that informal consolidation occurs for Abnaul Khairaat. Sharing stories about the old Guru's sacredness gave birth to a close relationship (cohesiveness) among the Alkhairaat masses. The sacred story of the Old Teacher became a discussion among haul participants because everyone who lived with him had a different experience with others who were also Old Master's students. The experience of each follower of the Old Teacher, met in the haul arena. That is called convergence. Sharing fantasy themes in the Old Teacher's Haul became a venue for silaturrahim narratives, which strengthened the Alkhairaat organization. The love for old teachers is implemented in the form of love for Alkhairaat community organizations.